FORMATION OF SCIENTIFIC CONCEPTS ABOUT INTUITION (Web of Teachers: Inderscience Research, 2025)
In this article, the formation of scientific concepts about intuition and creativity is the activity of the human psyche, the creative abilities of a person. As a result of creativity, material and spiritual values of social importance are created, previously unknown facts, features, laws are discovered, new methods of cognition and the assimilation of the universe are developed, scientific conclusions of the expected results have been drawn.